2021
DOI: 10.21037/atm-20-1369
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative planning for intraoperative navigation guidance

Abstract: Intraoperative navigation for spinal procedures has continued to gain popularity. Numerous platforms are currently on the market and offer a spectrum of features. Preoperative considerations when utilizing this technology begin with understanding the fundamental concepts and methods of navigation.Several key factors including patient positioning, reference array placement, and sequence of instrumentation can help improve intraoperative navigation workflow when planned appropriately. The authors review current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, these methods introduced increased radiation exposure, trajectory failure, and other pitfalls that were primarily addressed with the coming together of robotics with navigation. Even with the limitations associated with stand-alone robotic assistance, studies have reported favorable results regarding the accuracy of pedicle screw insertions in the range of 94.5% and 99% [37,40,[50][51][52]. One study investigating floormounted robotic pedicle screw placement found pedicle screw accuracy in 229 patients with 1050 screws to be 96.4% [53].…”
Section: Advanced Systems and Clinical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these methods introduced increased radiation exposure, trajectory failure, and other pitfalls that were primarily addressed with the coming together of robotics with navigation. Even with the limitations associated with stand-alone robotic assistance, studies have reported favorable results regarding the accuracy of pedicle screw insertions in the range of 94.5% and 99% [37,40,[50][51][52]. One study investigating floormounted robotic pedicle screw placement found pedicle screw accuracy in 229 patients with 1050 screws to be 96.4% [53].…”
Section: Advanced Systems and Clinical Resultsmentioning
confidence: 99%
“…Systems considered active navigation are restrictive to surgical movements that deviate from predetermined paths set in the presurgical planning stage of the procedure. Imagebased systems incorporating active navigation components, such as in robotics or drilling guides, utilize a predetermined trajectory set during the preoperative planning stage of the process [40].…”
Section: Active Versus Passive Navigation In Image-guided Surgerymentioning
confidence: 99%
“…Since there are multiple foreign bodies in the patient's body, preoperative preparations are made to remove them. Topographic anatomy surgery planning uses optical markers placed at anatomical landmarks on the body [ 5 ]. In this method, a previously obtained CT scan is used to determine the location of these foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
“…It is strongly necessary to assess the preoperative anatomical changes of cervical kyphosis using a 3D CT scan. For patients with severe cervical anatomical deformity, intraoperative CT navigation can enhance the safety of surgery ( Sabri and York, 2021 ). Successful lateral mass screw placement still highly depends on the surgeon’s experience.…”
Section: Discussionmentioning
confidence: 99%